Rate effects on fiber–matrix interfacial transverse debonding behavior. (February 2020) - Chu, Jou-Mei; Claus, Benjamin; Lim, Boon Him; O'Brien, Daniel; Sun, Tao; Fezzaa, Kamel; Chen, Wayne
The rate effect of fiber–matrix interfacial debonding behavior of SC-15 epoxy with S-2 glass and aramid fiber reinforcements was studied via in-situ visualization of the transverse debonding event. In this study, the debonding force history, debonding initiation, debonding crack velocity, and crack geometry were characterized using a quasi-static load frame and a modified tension Kolsky bar at loading velocities of 0.25 mm/s and 2.5 m/s. Cruciform-shaped specimens were used for interfacial transverse debonding between SC-15 epoxy matrix and two types of fiber reinforcements. The load history and high-speed images of the debonding event were simultaneously recorded. A major increase was observed for the average peak debonding force and a minor increase was observed for the average crack velocity with increasing loading velocity. The crack geometry of the cruciform specimens under both loading velocities was also tracked. Scanning electron microscopy of the recovered specimens revealed the debonding direction along the fiber–matrix interface through angled patterns on the failure surface.